Análisis de los cambios efectuados en la regulación de los servicios de telecomunicaciones y consecuencias sobre un isp a julio 2009. - Zambrano Cantos, Krystel (2009)
This project is an analysis of changes in the regulation of telecommunications services and the effects they have had on ISPs. Our research has been conducted based on information obtained up until July 2009. The purpose of this research and analysis is to show the current status of telecommunication regulations in the country and how they lead to continual changes for individual users and businesses. In our research, we analyzed Ecuadorian laws relating to the telecommunications sector, and we also looked at how these regulations have changed and evolved over time. Also, we identified key players in the telecommunications sector, detailing each of the roles they play in today's market. Finally, we analyzed current issues facing ISPs, such as limitations and restrictions on obtaining permits, which ISPs need to in order to perform their services. We also discussed possible solutions to these issues.